2020
DOI: 10.3389/fpsyg.2020.603117
|View full text |Cite
|
Sign up to set email alerts
|

Time Pressure and In-group Favoritism in a Minimal Group Paradigm

Abstract: Based on the group heuristic model and the model of intuitive cooperation, we hypothesized that in-group favoritism would be conspicuously shown through an intuitive process. To test this hypothesis, we utilized a minimal group paradigm, which is traditionally used in social psychological studies, and manipulated decision time in a one-shot prisoner’s dilemma game to compare the cooperative contribution level toward in-group and out-group members under three conditions: intuitive, empathic deliberation, and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…One possible explanation is that individuals’ prosocial decision-making depends on who they interact with. For example, Maeda and Hashimoto (2020) found that although individuals may be intuitive cooperators, they tended to act more cooperatively with their in-group members than with out-group members. However, on the other hand, the results showed that the impact of RSA reactivity on the amount of third-party punishment was still influenced by social value orientation (i.e., prosocial or self-orientation).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that individuals’ prosocial decision-making depends on who they interact with. For example, Maeda and Hashimoto (2020) found that although individuals may be intuitive cooperators, they tended to act more cooperatively with their in-group members than with out-group members. However, on the other hand, the results showed that the impact of RSA reactivity on the amount of third-party punishment was still influenced by social value orientation (i.e., prosocial or self-orientation).…”
Section: Discussionmentioning
confidence: 99%
“…Second, future research should focus on the people they cooperate with, or what kind of social exchange is assumed by the decision-makers. The possibility that people intuitively process information in a way that aims for mutual cooperation has been pointed out before: the possibility that intuitive mutual cooperation may work as an adaptive strategy to the general exchange system within a group (e.g., Yamagishi et al, 2007) or that intuitive cooperation may work only for members of an ingroup (Maeda & Hashimoto, 2020). Finally, the present study examined the difference in cooperation rates through experimental manipulations with a transformed matrix, and although the results did not support our hypothesis, the robustness of our results needs to be confirmed by simultaneous manipulation of decision time and interaction partners.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a similar three-way interaction showed a medium effect size (partial η 2 = 0.06) in our recent work [ 4 ] when two groups each contain 25 participants. Finally, previous behaviour research on fairness norm enforcement had a similar sample size per condition [ 46 , 47 ]. All participants were right-handed and did not report any psychiatric or neurological disorders.…”
Section: Studymentioning
confidence: 99%